Utilization of Recycled Paper Sludge (RPS) In Production of Sand Cement Bricks - MUSTAFA, DANIAL; Ahmad Jeni, Mohamad Luthfi; Kosnin, Hilmi (Progress in Engineering Application and Technology, 2023)
As we know, Malaysia is a country that currently one of the fast developing countries in the world, so a lot of construction work is currently undergoing in Malaysia. Sand cement brick production was increased as linear with the growing of urbanization and economy in Malaysia. However, an issue of waste papers in Malaysia come out because a lots of waste paper been produce every day. The challenge was to find out the alternative way to use all the waste paper in the construction industries. There lots of studies have been conducted in order to replace the fine aggregate in sand cement brick mix with the waste materials. Therefore, this study was to promote utilization of Recycle Paper Sludge (RPS) with different percentages of RPS in producing sand cement brick. The main objectives of the study was to find the mechanical properties of the bricks mixture containing Recycled paper sludge (RPS) as replacement material of sand. In this study, we use 0%, 3%, 5%, 10% and 15% of RPS as a partial replacement to sand in the mixture of sand cement brick. The experiments that were conducted were density, water absorption, compressive strength, thermal conductivity and sound absorption coefficient. From the result obtained it can conclude that the used of the Recycled Paper Sludge (RPS) in the mixture of the sand cement bricks will save the cost of the production of bricks and produce an eco-friendly brick. Furthermore, recycled paper sludge in the mixture of sand brick material can increase the workability and the strength of the sand brick which will give the best recommendation for the construction industry